A critical review of waste glass powder – Multiple roles of utilization in cement-based materials and construction products. (15th July 2019) - Jiang, Yi; Ling, Tung-Chai; Mo, Kim Hung; Shi, Caijun
Abstract: In light of concerns relating to improper waste disposal and resources preservation, reclamation of the discarded glass in construction materials had been extensively carried out since 1963. In the past decade, although more than 100 papers associated with the use of glass powder (GP) in the micron level scale were published, comprehensive review of all practical applications in cement-based materials and construction products is not available. This paper therefore provides a summary of the body of knowledge on the interaction and effects of using GP in cement-based and extended construction materials. This review concludes that GP is an innovative and promising eco-supplementary cementitious material. Beyond that, use of GP is demonstrated to be potentially beneficial as a precursor in geopolymer and suitable for manufacturing eco-cement, artificial lightweight aggregate and composite phase change material. The multiple applications of GP are seen as an important step towards waste glass recycling as a sustainable construction material and for the overall betterment of the industry. Highlights: Glass powder (GP) is a reactive pozzolan and effective ASR inhibitor. GP can enhance the properties of concrete with selective particle size and dosage. GP can facilitate the geopolymerization process of alkali activated materials. GP can be innovatively used to produce sintering and heat storage products.